Pengembangan LKPD Berbasis PBL pada Materi IPAS Keragaman Flora dan Fauna Indonesia Kelas V : Indonesia - Nadia Nanda Nusnida; Sukriadi; Taufik Hidayat; Iksam (Universitas Ngudi Waluyo, 2025)
Abstract This study aims to develop a Student Worksheet (LKPD) based on Problem-Based Learning (PBL) to develop and test the feasibility of IPAS (Science and Social Science) instruction. The research was motivated by the lack of diverse teaching materials used in SD Negeri 008 Samarinda Ilir, which results in students becoming passive and less engaged during lessons. To address this, innovative and contextual learning resources are needed. The PBL model, which focuses on student-centered learning and solving real-life problems, offers a promising solution. The development process followed the Research and Development (R&D) approach, employing the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were gathered through questionnaires, interviews, and classroom observations. Instruments included validation sheets assessed by subject matter experts, media experts, language experts, and student feedback forms. The participants were fifth-grade students at SD Negeri 008 Samarinda Ilir. The results indicated that the developed PBL-based LKPD met validity standards, with expert validation scores ranging from 82% to 94.66%, all categorized as “very valid.” Feasibility was confirmed through student response questionnaires, showing 83.23% in small group trials and 89.95% in large group trials. Overall, the PBL-based LKPD is a highly appropriate learning tool for teaching Indonesia’s flora and fauna diversity in IPAS. Abstrak Penelitian ini bertujuan untuk mengembangkan dan menguji kelayakan Lembar Kerja Peserta Didik (LKPD) berbasis Problem Based Learning (PBL) pada pembelajaran IPAS (Ilmu Pengetahuan Alam dan Sosial). Latar belakang penelitian ini adalah kurangnya variasi bahan ajar yang digunakan di SD Negeri 008 Samarinda Ilir, yang menyebabkan peserta didik menjadi pasif dan kurang terlibat dalam proses pembelajaran. Untuk mengatasi hal ini, dibutuhkan sumber belajar yang inovatif dan kontekstual. Model PBL yang berpusat pada peserta didik dan menekankan pemecahan masalah nyata dinilai sebagai solusi yang tepat. Pengembangan LKPD ini menggunakan metode Research and Development (R&D) dengan model ADDIE yang terdiri dari lima tahap: Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Pengumpulan data dilakukan melalui angket, wawancara, dan observasi kelas. Instrumen yang digunakan mencakup lembar validasi dari ahli materi, ahli media, ahli bahasa, serta angket tanggapan peserta didik. Subjek dalam penelitian ini adalah peserta didik kelas V SD Negeri 008 Samarinda Ilir. Hasil penelitian menunjukkan bahwa LKPD berbasis PBL yang dikembangkan memenuhi standar validitas, dengan skor validasi dari para ahli berkisar antara 82% hingga 94,66%, yang semuanya termasuk kategori